"In and out of crisis": life course criminalization for jefas in the barrio - Maldonado-Fabela, Katherine L. (Critical criminology, 2022)
Scholars have documented how violence, criminalization, and other forms of control impact the life trajectories of criminalized women. Less research exists on the ways that processes of criminalization affect the health of mothers across the life course. This study examines how the legal constructions of criminalized labels such as gang affiliation, are a process of long-term violence and threat of violence and second, how short and long-term criminalization affects family health-what I refer to as life course criminalization. This qualitative study is based on photo elicitation life history testimonios with 13 gang affiliated, system-impacted Chicana/Latina mothers from South Central Los Angeles, California and connects life course theory with feminist abolitionist decolonial perspectives. It documents how crises perpetuated by multi-institutional violence and other forms of violence influence relations between legal, social, and health related experiences for system-impacted mothers and their families. Through their testimonios they show the intergenerational mechanisms that connect the body’s health, family surveillance, and criminalization processes to survival, and spiritual resistance.